2013
DOI: 10.1016/j.scijus.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical enhancement of footwear impressions in blood on fabric — Part 3: Amino acid staining

Abstract: Enhancement of footwear impressions, using ninhydrin or ninhydrin analogues is not considered common practice and such techniques are generally used to target amino acids present in fingermarks where the reaction gives rise to colour and possibly fluorescence. Ninhydrin and two of its analogues were used for the enhancement of footwear impressions in blood on various types, colours and porosities of fabric. Test footwear impressions on fabric were prepared using a specifically built rig to minimise the variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Blood-contaminated fingermarks are a key evidence for forensic investigators in high-profile cases providing a direct link between the suspect and the crime [1]. Although these marks are often visible, further enhancement techniques are commonly required to recover maximal ridge detail [2][3][4]. Usually, blood-contaminated fingermarks are enhanced by the application of protein staining reagents and require, as a first step, a blood-fixing process [5].…”
Section: Introductionmentioning
confidence: 99%
“…Blood-contaminated fingermarks are a key evidence for forensic investigators in high-profile cases providing a direct link between the suspect and the crime [1]. Although these marks are often visible, further enhancement techniques are commonly required to recover maximal ridge detail [2][3][4]. Usually, blood-contaminated fingermarks are enhanced by the application of protein staining reagents and require, as a first step, a blood-fixing process [5].…”
Section: Introductionmentioning
confidence: 99%
“…The use of DFO did not provide any positive enhancements and in most cases there was a deterioration of the original mark. Previous studies have suggested that the use of DFO for the enhancement of marks made in blood may be hindered by the surface of the substrate and associated fluorescence quenching where the enhancement of footwear impressions in blood on fabric with DFO was found to be ineffective [12]. This appears to be contrary to other studies where DFO was found to be extremely sensitive for the development of fingermarks in blood on porous surfaces and also produced highly fluorescent marks with the lightest marks [10].…”
Section: Evaluation Of Enhancement Techniquesmentioning
confidence: 85%
“…A study [6] of the enhancement of footwear impressions in blood on various surfaces demonstrated that ninhydrin can yield good quality marks displaying clear pattern details. Ninhydrin was also successful in enhancing footwear impressions in blood on paper that had been exposed to rain for over three weeks [7] as well as footwear marks in blood on different types of fabric [8]. The successful use of ninhydrin and DFO for the treatment of stains in blood followed by successful subsequent DNA typing has also been demonstrated [9][10].…”
Section: Ninhydrin and Dfomentioning
confidence: 99%